A gender-based comparison of intermolar width conducted at Padjajaran University Dental Hospital, Bandung, Indonesia - Adriana Azlan; Endah Mardiati; Ida Ayu Evangelina (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Evaluation of dental arches is important for both diagnosis and treatment in the fields of orthodontics, prosthodontics, and forensics. The perimeter or circumference affects the gender-specific dimensions of the dental arch. Purpose: To identify the inter-gender difference between maxillary and mandibular intermolar width of the first molars in Indonesia. Methods: This retrospective and comparative analytical study involved a gender-based comparison of maxillary and mandibular intermolar width in the first molars. A purposive sampling technique was employed for data selection. Ninety dental cast models were selected according to the inclusion criteria of non-growing patients and perfect dental conditions, with any damaged dental models being rejected. After selection, the dental cast was marked at the maxillary and mandibular first molar central fossae before being measured three times with a digital vernier caliper. The data obtained was subsequently analyzed by means of a Kolmogorov-Smirnov test, an F-test-Snedecor (with p>0.05) and Independent Sample t-test (with p<0.05). Results: The average maxilla intermolar widths for males and females were 49.36mm and 46.75mm respectively, while the average mandibular intermolar widths for males and females were 43.17mm and 40.5mm. An independent sample t-test showed that the maxilla and mandibular intermolar widths were significantly different for males and females (p=0.000, p<0.05), with male subjects possessing a higher value than female subjects. Conclusion: A significant gender-based difference existed between the maxillary and mandibular intermolar width of patients attending Padjadjaran University Dental Hospital, Bandung, Indonesia.